A phase 1/2, open‐label, multicenter study of isatuximab in combination with cemiplimab in patients with lymphoma. Issue 1 (31st October 2022) - Carlo‐Stella, Carmelo; Zinzani, Pier Luigi; Sureda, Anna; Araújo, Luis; Casasnovas, Olivier; Carpio, Cecilia; Yeh, Su‐Peng; Bouabdallah, Krimo; Cartron, Guillaume; Kim, Won Seog; Cordoba, Raul; Koh, Youngil; et al.
Abstract: Patients with relapsed or refractory lymphoma have limited treatment options, requiring newer regimens. In this Phase 1/2 study (NCT03769181), we assessed the safety, efficacy, and pharmacokinetics of isatuximab (Isa, anti‐CD38 antibody) in combination with cemiplimab (Cemi, anti‐programmed death‐1 [PD‐1] receptor antibody; Isa + Cemi) in patients with classic Hodgkin lymphoma (cHL), diffuse large B‐cell lymphoma (DLBCL), and peripheral T‐cell lymphoma (PTCL). In Phase 1, we characterized the safety and tolerability of Isa + Cemi with planned dose de‐escalation to determine the recommended Phase 2 dose (RP2D). Six patients in each cohort were treated with a starting dose of Isa + Cemi to determine the RP2D. In Phase 2, the primary endpoints were complete response in Cohort A1 (cHL anti‐PD‐1/programmed death‐ligand 1 [PD‐L1] naïve), and objective response rate in Cohorts A2 (cHL anti‐PD‐1/PD‐L1 progressors), B (DLBCL), and C (PTCL). An interim analysis was performed when the first 18 (Cohort A1), 12 (Cohort A2), 17 (Cohort B), and 11 (Cohort C) patients in Phase 2 had been treated and followed up for 24 weeks. Isa + Cemi demonstrated a manageable safety profile with no new safety signals. No dose‐limiting toxicities were observed at the starting dose; thus, the starting dose of each drug was confirmed as the RP2D. Based on the Lugano 2014 criteria, 55.6% (Cohort A1), 33.3% (Cohort A2), 5.9% (Cohort B), and 9.1% (Cohort C) of patients achieved a complete or partial response. Pharmacokinetic analyses suggested no effect of Cemi on Isa exposure. Modest clinical efficacy was observed in patients with cHL regardless of prior anti‐PD‐1/PD‐L1 exposure. In DLBCL or PTCL cohorts, interim efficacy analysis results did not meet prespecified criteria to continue enrollment in Phase 2 Stage 2. Isa + Cemi did not have a synergistic effect in these patient populations.